Alastair Small and Carola Small (eds) Archaeology on the Apulian-Lucanian Border. - Attema, Peter (Journal of Greek Archaeology, 2025)
This substantial monograph of almost 900 pages presents the results of the intensive Basentello Valley Field Survey, led by the authors between 1996 and 2008 in the Fossa Bradanica region on the border of the Basilicata (Lucania) and Puglia (Apulia) regions in South Italy (roughly between the present-day cities of Bari on the coast and Potenza inland).